Opportunities and Challenges for Chinese Elderly Care Industry in Smart Environment Based on Occupants’ Needs and Preferences - Meng, Qingfeng; Hong, Ziming; Li, Zhen; Hu, Xin; Shi, Weixiang; Wang, Jun; Luo, Kai (Frontiers in Psychology, 2020)
New developments in intelligent devices for assisting elderly people can provide them with friendly, mutual and personalized interactions. Since the intelligent devices should continually make an important contribution to smart elderly care industry and smart services or policies for caring the elders are recently provided by a large number of government programs in China. At present, the smart elderly care industry in China has attracted numerous investors’ attention, but the smart elderly care industry in China is still at the beginning stage. Though there are great opportunities in the market, many challenges and limitations still need to be solved. This study analyzes 198 news reports about opportunities and challenges in smart elderly care industry from six major Chinese portals. The analysis is mainly based on needs assessment for elderly people, service provider and China’s government. It is concluded that smart elderly care services are a promising way to satisfy the elders’ mental wants and then needs for improving modernization services are the most frequently mentioned opportunities. Besides, the frequently mentioned challenges behind opportunities are gaps between elders’ strong demand and limitations of intelligent devices; negative attitudes toward consuming goods in elders; the limited financial ability to pay in low-income elders. The results of this study will enable stakeholders in the smart elderly care industry to clearly understand opportunities and challenges influenced by the rapid development of modernization in China. So it is expected to provide a theoretical basis for the industry decision-makers and allow them to make better decisions.